Substance Use Disorders and COVID-19: Multi-Faceted Problems Which Require Multi-Pronged Solutions - Jemberie, Wossenseged Birhane; Stewart Williams, Jennifer; Eriksson, Malin; Grönlund, Ann-Sofie; Ng, Nawi; Blom Nilsson, Marcus; Padyab, Mojgan; Priest, Kelsey Caroline; Sandlund, Mikael; Snellman, Fredrik; McCarty, Dennis; Lundgren, Lena M. (Frontiers in Psychiatry, 2020)
COVID-19 shocked health and economic systems leaving millions of people without employment and safety nets. The pandemic disproportionately affects people with substance use disorders (SUDs) due to the collision between SUDs and COVID-19. Comorbidities and risk environments for SUDs are likely risk factors for COVID-19. The pandemic, in turn, diminishes resources that people with SUD need for their recovery and well-being. This article presents an interdisciplinary and international perspective on how COVID-19 and the related systemic shock impact on individuals with SUDs directly and indirectly. We highlight a need to understand SUDs as biopsychosocial disorders and use evidence-based policies to destigmatize SUDs. We recommend a suite of multi-sectorial actions and strategies to strengthen, modernize and complement addiction care systems which will become resilient and responsive to future systemic shocks similar to the COVID-19 pandemic.